2013
DOI: 10.1590/s0034-75902013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Produção científica brasileira em gestão de operações no período 2000-2010

Abstract: Este estudo analisa temas e métodos de pesquisa trata-tes nos artigos analisados, houve convergência entre o dos por pesquisadores brasileiros da área de Gestão de que foi publicado pelos autores brasileiros no Brasil e Operações por meio de dois vetores complementares: a nos periódicos estrangeiros, com destaque para supply relevância e o rigor. Inicialmente, contemplaram-se os chain management e estratégia de operações. No que últimos 10 anos das principais revistas brasileiras da área tange ao rigor metodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(13 reference statements)
0
3
0
6
Order By: Relevance
“…Os temas Gestão de Operações e Gestão de Operações de Serviço foram pauta de várias revisões que buscaram descrever a evolução e características do campo (BUFFA, 1980;AMOAKO-GYAMPAH e MEREDITH, 1989;PANNIRSELVAM et al, 1999;ARKADER, 2003;CORREA et al, 2010;PAIVA E BRITO, 2013). Porém, pouca atenção foi dada a análises específicas do setor público.…”
Section: Resultsunclassified
“…Os temas Gestão de Operações e Gestão de Operações de Serviço foram pauta de várias revisões que buscaram descrever a evolução e características do campo (BUFFA, 1980;AMOAKO-GYAMPAH e MEREDITH, 1989;PANNIRSELVAM et al, 1999;ARKADER, 2003;CORREA et al, 2010;PAIVA E BRITO, 2013). Porém, pouca atenção foi dada a análises específicas do setor público.…”
Section: Resultsunclassified
“…Five papers were published there that, in addition to other findings and recommendations, map the themes that were discussed in the papers published in the country's scientific journals for the following areas: Organizational Behavior (SOBRAL; MANSUR, 2013), Human Resource Management (MASCARENHAS; BARBOSA, 2013), Finance (LEAL et. al., 2013), Operations Management (PAIVA and BRITO, 2013) and Marketing (MAZZON;HERNANDEZ, 2013). Beuren et al (2007) Cardoso et al (2007) also used the thematic classification proposed by ANPAD in a profile analysis of the cost accounting studies presented in EnANPAD between 1998 and In an analysis of the scientific research in information systems produced between 1990 and 2003, Hoppen and Meirelles (2005) structured a mapping framework for the addressed themes following a classification scheme for the IS literature proposed by Barki et al (1993) consisting of nine main themes.…”
Section: The Practice Of Mapping and Classifying Study Themesmentioning
confidence: 99%
“…The concern with service operations management has rightly increased in academic circles, reflecting the migration of a large number of manufacturing jobs to the service area. Paiva and Brito (2013) identified that the topics supply chain management and operations strategy occupy the first positions among the topics of interest of the operations management academic community in Brazil, possibly because these topics interface with other areas of business administration. The topic service operations appears as the fourth most discussed in the national scientific journals they assessed.…”
mentioning
confidence: 99%
“…Although the study by Paiva and Brito (2013) found a significant reduction in recent interest in quality management, its extensive discussion throughout the 1990s may have contributed to the shift of operations management research to "softer" themes. "Harder" topics, more related to engineering and manufacturing-a characteristic identified by Corrêa et al (2010)-have gradually given way to concerns that are more related to management, its declared purpose since it was still known as production administration; and finally, to service operations topics.…”
mentioning
confidence: 99%